The Cambridge history of Southeast Asia - Tarling, Nicholas editor (Cambridge : Cambridge UNiversity Press, 1990)
Contents: volume one, part one: From early times to c1500; volume one, part two: from c1500 to c1800; volume two, part one: from c1800 to the 1930s; and volume two, part two: from World War II to present
Keywords: Asia, Southeastern -- History